Penerapan Media Pembelajaran Kartu Permainan Sejarah dalam Meningkatkan Keaktifan Belajar Peserta Didik (Studi kasus pada Kelas X-TKJ SMK Wahdatul Jannah Majalengka) - Galun Eka Gemini (LP4MK STKIP PGRI Lubuklinggau, 2019)
History is often addressed by most learners as boring subjects. It appears from the passive attitude of learners during the learning process takes place, such as the lack of activity to ask, respond and answer questions from the teacher. Therefore, learning is more on teacher centered patterns, centered on teachers. This is feared to cause misperception-what the teacher tells the learners, so that learners do not fully accept the material well. Such facts encouraged this research. Researchers are trying to improve the learning conditions in X-TKJ SWK Wahdatul Jannah class through the application of historical game card media. The main purpose of this study is to improve the learning activities of learners. Game card game history is packed through group discussions and class discussions. This research is a Class Action Research (PTK), consisting of three cycles. Selection of class X-TKJ SMK Wahdaul Jannah as the object of research dilatari because in the classroom learning process (history) less so interactive, the relationship between teachers with learners. As for the results obtained, the cycle 1 learning activeness of students showed increased learning activeness ranged 54%, cycle 2 learning activeness learners increased 70%, cycle 3 learning activeness learners increased 82%. Thus, the use of history card game media is said to be successful as an effort to improve the learning activities of learners.